City Branding of Luleå : From the Perspective of Luleå Municipality and Exchange Students at Luleå University of Technology - Rova, Linn; Österhult, Sanna (2013)
This thesis is about how exchange students perceive Luleå’s city branding but also to see how much Luleå municipality is visible towards students. By connecting the decision-making-process that the exchange students have had before arriving in Luleå, it is possible to see if the exchange students choose a location for educational purposes or tourism attractions. Luleå municipality has during a period of time focused on city branding through different media to reach a broader crowd. By connecting to exchange students it was interesting to see if the city branding has affected the exchange students in their decision-making-process to study in Luleå and at LUT. Glover (2011) used a framework that describes students’ process of deciding to go abroad, either for educational purposes or for tourism attractions. The Glover model (2011) also added Mazzarol and Soutar’s push- and pull strategy (2002) that consists of different factors that can affect a student decision-making-process. This thesis main foundation lies in the Glover model (2011) and the push and pulls factors that Mazzarol and Soutar (2002) state. Therefore, the results of this research are that it is a mixture of educational and tourism attractions which make the exchange students choose Luleå and LUT for their period abroad. The main reason why the exchange students choose Luleå and LUT was because of the friendship deal between the niversities. This indicates, together with the fact that students who decide to study abroad usually decides this prior to gathering information, that the model can be improved since it does not show the reality properly. Additionally, the city branding that Luleå has worked with for a period of time has not reached exchange students. This can be because Luleå municipality has not targeted exchange students as a group in their marketing strategy. Validerat; 20130621 (global_studentproject_submitter)